1979
DOI: 10.1161/01.res.45.5.666
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotonic activity of amrinone--Win 40680 [5-amino-3,4'-bipyridine-6(1H)-one].

Abstract: SUMMARYThe cardiotonic activity of a new, noncatechol, nonglycoside agent, amrinone, waa investigated in vitro and in anesthestized and unanesthetized dogs. Amrinone (3-1000 /ig/ml) caused a dose-dependent increase in papillary muscle developed tension and df/dt without significant changes in duration of the contractile cycle or time-to-peak tension. Amrinone induced slight increases in right atrial rate with no changes in electrophysiological properties of the cat papillary muscle or dog Purkinje fibers. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
0

Year Published

1984
1984
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(38 citation statements)
references
References 29 publications
4
34
0
Order By: Relevance
“…Increases in HR induced by amrinone (Alousi et al, 1979;Zannad et al, 1983;Sato et al, 1986) and dobutamine (Tuttle & Mills, 1975;Sonnenblick et al, 1979) have been reported previously and lack of direct chronotropic effect of OPC-18790 is also consistent with a previously reported action in canine isolated right atria (Hosokawa et al, 1992). From the parameters of cardiac energetics elucidated by 3'P-MRS signals, it is shown that amrinone and dobutamine aggravate the cardiac energetic state, namely increase Pi, decrease PCr and ATP and cause further acidification of intracellular pH, with an increase in LVdP/dt (Figure 4).…”
Section: Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increases in HR induced by amrinone (Alousi et al, 1979;Zannad et al, 1983;Sato et al, 1986) and dobutamine (Tuttle & Mills, 1975;Sonnenblick et al, 1979) have been reported previously and lack of direct chronotropic effect of OPC-18790 is also consistent with a previously reported action in canine isolated right atria (Hosokawa et al, 1992). From the parameters of cardiac energetics elucidated by 3'P-MRS signals, it is shown that amrinone and dobutamine aggravate the cardiac energetic state, namely increase Pi, decrease PCr and ATP and cause further acidification of intracellular pH, with an increase in LVdP/dt (Figure 4).…”
Section: Drugsmentioning
confidence: 99%
“…Therefore, the usefulness of these drugs in the ischaemic heart is determined by the balance of these actions. In fact, deleterious effects of positive inotropic stimulation in ischaemic hearts have been reported (Rude et al, 1980;Pozen et al, 1981 (Taira, 1987), many are guanosine 3': 5'-cyclic monophosphate (cyclic GMP)-inhibited phosphodiesterase (cGI-PDE) inhibitors such as amrinone (Alousi et al, 1979). Recently, we described a new compound, OPC-18790 [(± )-6-[3-(3,4-dimethoxybenzylamino)-2-hydroxypropoxy]-2-(lH)-quinolinone] (Fujioka et al, 1992) which is a Author for correspondence.…”
Section: Introductionmentioning
confidence: 99%
“…Amrinone (5-amino-3,4-bipyridin-6(l H)-one; Win 40680) decreases peripheral vascular resistance and increases cardiac output and contractility in a variety ofin vitro and in vivo preparations (Benotti et al, 1978;Alousi & Farah, 1978;LeJemtel et al, 1979;Klein et al, 1981;Ward et al, 1983;Toda et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Selective phosphodiesteraseIII (PDEIII) inhibitors such as amrinone (AM) and milrinone (ML) increase the intracellular concentration of cyclic adenosine-3, 5-cyclic monophosphate (cAMP) [8] by inhibiting PDEIII, which is a splitting enzyme of cAMP [37] and increase myocardial contractility without activation of adrenergic receptors [1,2]. Therefore PDEIII inhibitors might act effectively even in the case that CAs do not act adequately due to adrenergic receptor down regulation [6].…”
mentioning
confidence: 99%